2(k-1)=34(-k-2)

Simple and best practice solution for 2(k-1)=34(-k-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(k-1)=34(-k-2) equation:


Simplifying
2(k + -1) = 34(-1k + -2)

Reorder the terms:
2(-1 + k) = 34(-1k + -2)
(-1 * 2 + k * 2) = 34(-1k + -2)
(-2 + 2k) = 34(-1k + -2)

Reorder the terms:
-2 + 2k = 34(-2 + -1k)
-2 + 2k = (-2 * 34 + -1k * 34)
-2 + 2k = (-68 + -34k)

Solving
-2 + 2k = -68 + -34k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '34k' to each side of the equation.
-2 + 2k + 34k = -68 + -34k + 34k

Combine like terms: 2k + 34k = 36k
-2 + 36k = -68 + -34k + 34k

Combine like terms: -34k + 34k = 0
-2 + 36k = -68 + 0
-2 + 36k = -68

Add '2' to each side of the equation.
-2 + 2 + 36k = -68 + 2

Combine like terms: -2 + 2 = 0
0 + 36k = -68 + 2
36k = -68 + 2

Combine like terms: -68 + 2 = -66
36k = -66

Divide each side by '36'.
k = -1.833333333

Simplifying
k = -1.833333333

See similar equations:

| -3(-2x+4)+-2(x-5)= | | 5(2x-4)-3(2x+1)=12 | | 4.2+1.8(2x+3)=45.6 | | (4x-5)^2=(3x+2)(8x-10) | | 3t^2+9t+3=0 | | 2/3=-1s/3 | | 2a+7/4a^2+1 | | 7x+9=100 | | 2(a-4)=49-(29+4) | | N(3+2)+6=5n+(10-3) | | 4x^2-24x-2 | | -8(2a-3b)-5(6b-4a) | | 4y+7=51 | | 1/4(x+2)=8 | | 6times9 | | x-12÷6=9= | | 2x+x-1+2x+2x-3+x=76 | | 3+1(y-4)=2(1-y) | | (3x+5)=5x=2 | | 6x-4=4x+10 | | (n+18)squared=576 | | 8x-3-4x=9+4x-12 | | 67-5x=4x+17 | | -9+-3= | | .34x+1.6=.425(x+5)-.2 | | 6x+3-4x=4x+5 | | 50/x=10 | | 3x-x=30-12 | | 6-(3x-4)=-x-6 | | 108-3x=3x | | 6+2x=3+x | | 6x-5=6x |

Equations solver categories